CULTIVATING CHARACTER BUILDING IN WRITING CLASSES THROUGH YOU TUBE VIDEOS. IS IT POSSIBLE? - Lestari Setyowati (JURNAL DIMENSI PENDIDIKAN DAN PEMBELAJARAN, 2017)
ABSTRACTWith todays technology advancement, it is a requirement for teachers to be familiar with Information Technology (IT) world. One of the ITs which can be maximized in ELT classroom is You Tube. However, not many ELT teachers have adequate knowledge on how to use You Tube to teach English, especially writing. You Tube  is a free and rich learning tools that can be used to teach writing and at the same time, if it is planned and used properly, raise the students’ positive characters. Since many of the EFL students feel that writing is a demanding and difficult subject, writing teachers need to connect the topic of the composition with life outside the classroom. Thus, You Tube serves as an excellent tool to relate the topic in writing classes and life outside school. This paper is intended to addresses various ways teachers can use the video website YouTube.com (or other online streaming video websites) to teach English, especially in writing, and which part of character building which can be triggered from the use of particular kind of You Tube videos. Key Words: You Tube, writing, character building